Elevation of enterococcus-specific antibodies associated with bacterial translocation is predictive of survival rate in chronic liver disease - Iwasa, Motoh; Eguchi, Akiko; Tamai, Yasuyuki; Shigefuku, Ryuta; Nakagawa, Ryo; Hasegawa, Hiroshi; Kondo, Jumpei; Morikawa, Masayuki; Miyoshi, Eiji; Nakagawa, Hayato (Frontiers in Medicine, 2022)
Introduction/Purpose: The gut-liver axis contributes to disease progression, a rise in infection rate, organ failure and a poor overall outcome in chronic liver diseases. Monitoring of the gut-liver axis is critical in understanding disease status, but biomarkers have not been elucidated. The aim of this study is to determine the level of serum antibodies against Enterococcus (E.) faecalis in evaluating patients with chronic liver diseases (CLD), including those treated with rifaximin (a minimally absorbed antibiotic), and in patients with alcohol-associated liver disease (ALD). Methods: We enrolled 109 CLD patients (cohort 1), 30 hepatic encephalopathy patients treated with rifaximin (cohort 2), 53 inpatients with ALD undergoing alcohol cessation (cohort 3) and 33 healthy subjects. To assess the consequences of E. faecalis translocation, we developed an assay for the detection of a serum antibody against E. faecalis capsular polysaccharide (E.CPS). Results: Serum E.CPS antibody titer was elevated only in those patients with advanced CLD and ALD. The E.CPS antibody titer was an independent prognostic factor (p <0.05), while Mac‐2 binding protein and albumin-bilirubin score were not independent predictors of survival. The improvement of predictive model in integrated factors was significant [continuous net reclassification index (value 0.699, p <0.05) and integrated discrimination improvement (value 0.164, p =0.051)]. Furthermore, rifaximin treatment led to a decrease of serum E.CPS antibody titer resulting in a significantly longer overall rate of survival. Conclusions: The E.CPS antibody titer appears to be a strong predictor of survival in CLD patients. Serum E.CPS levels decrease in CLD patients receiving rifaximin, and may be associated with an overall improvement in rate of survival.